Reparation: a sourcebook for victims of torture and other violations of human rights and international humanitarian law - Echeverria, Gabriela; Ferstman, Carla (The Redress Trust, 2003)
The Redress Trust has a very particular focus – we work with survivors of torture, and we try to assist them in their search for all forms of justice, and to ensure that their rights are recognised before national and international jurisdictions. Obtaining justice and other forms of reparation for torture and other international crimes is exceedingly difficult. There are many reasons for this. Firstly, these crimes normally imply and often require a certain level of State involvement. To obtain justice and redress implies that the State acknowledges responsibility and makes amends. In many instances, often for the very purpose of avoiding justice, there have been amnesty laws, shielding these crimes from prosecution. Often the perpetrators are supported by the States who should be punishing them; sometimes the perpetrators are even State officials. Sometimes the perpetrators flee their countries, and their country of exile has no interest to bring them to justice.
Keywords: Human rights; Redress; Refugees; Rehabilitation; Torture